Evaluation of genomic imprinting employing the analysis of Loss Of Imprinting (LOI) at the RNA level: preliminary results - Lamberti, Luca; Diplas, Andreas I.; Wetmur, James; Lee, Men-Jean; Chen, Jia (European Journal of Oncology and Environmental Health, 2009)
Aim. This manuscript summarizes the first results obtained on the investigation of the relationship between genomic imprinting dysregulation and intra-uterine growth restriction (IUGR). Genomic imprinting refers to the silencing of one parental allele in the zygotes depending upon the parent of origin; this silencing occurs via epigenetic processes such as DNA methylation and histone modification resulting in monoallelic expression of the affected genes in the offspring. Genomic imprinting plays a critical role in placental and fetal development. Emerging evidence implicates Loss Of Imprinting (LOI) in reproductive and developmental diseases, neurological disorders and cancer. IUGR accounts for 10% of all pregnancies in the US, it is associated with major postnatal morbidity and mortality in the newborn period and it has been associated with abnormalities in fetal growth that have been linked with developmental origins of many adult disorders, such as obesity and breast cancer. Some developmental syndromes have been moreover associated with known imprinted genes often seen in IUGR pregnancies that may therefore themself be associated with genomic imprinting dysregulation. Materials and Methods. We developed a functional and highly sensitive assay at the RNA level for measuring LOI. We also analyzed imprinted gene expression in normal and IUGR placentas by real-time PCR. Results. We showed that LOI is a common phenomenon in placenta that preferentially affects specific imprinted genes in IUGR compared to control placentas; however, this does not correlate with changes in expression of genes with a perturbed imprinting profile. Conclusions. Genomic imprinting dysregulation plays a role in the etiology of IUGR.